A Strobilurin Fungicide Enhances the Resistance of Tobacco against Tobacco Mosaic Virus and Pseudomonas syringae pv tabaci - Herms, Stefan (American Society of Plant Physiologists, 2002)
The strobilurin class of fungicides comprises a variety of synthetic plant-protecting compounds with broad-spectrum antifungal activity. In the present study, we demonstrate that a strobilurin fungicide, F 500 (Pyraclostrobin), enhances the resistance of tobacco (Nicotiana tabacum cv Xanthi nc) against infection by either tobacco mosaic virus (TMV) or the wildfire pathogen Pseudomonas syringae pv tabaci. F 500 was also active at enhancing TMV resistance in NahG transgenic tobacco plants unable to accumulate significant amounts of the endogenous inducer of enhanced disease resistance, salicylic acid (SA). This finding suggests that F 500 enhances TMV resistance in tobacco either by acting downstream of SA in the SA signaling mechanism or by functioning independently of SA. The latter assumption is the more likely because in infiltrated leaves, F 500 did not cause the accumulation of SA-inducible pathogenesis-related (PR)-1 proteins that often are used as conventional molecular markers for SA-induced disease resistance. However, accumulation of PR-1 proteins and the associated activation of the PR-1 genes were elicited upon TMV infection of tobacco leaves and both these responses were induced more rapidly in F 500-pretreated plants than in the water-pretreated controls. Taken together, our results suggest that F 500, in addition to exerting direct antifungal activity, may also protect plants by priming them for potentiated activation of subsequently pathogen-induced cellular defense responses.